2011
DOI: 10.1111/j.1365-2885.2010.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion study of three formulations of flumequine in edible tissues and drug transfer into chicken feathers

Abstract: To ensure the delivery of safe animal products to consumers, withdrawal times (WDT) of drugs must be respected. Drugs administered in therapies can also reach nonedible tissues (for humans) such as feathers; this transfer is of concern as feather meal is used in diets of food producing animals, being this a possible source of residue contamination of final products for human consumption. WDTs of three flumequine formulations (10%, 80% premix powder and 20% solution) as well as the transfer of this drug into fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…There is a need for methods that are able to detect the use of antibiotics administered over the entire life span of an animal, including treatments administered during the first days of the animals’ lives. In previous research focusing on the excretion of oxytetracycline [ 7 ], multiple fluoroquinolones (enrofloxacin, its metabolite ciprofloxacin [ 8 ], and flumequin [ 9 ]) and florfenicol and its metabolite florfenicol amine [ 10 ] to feathers, it has already been shown that antibiotic residues can still be detected in feathers long after treatment. In another study, different antibiotics in feather meal, originating from different countries, were detected, including antibiotics that are registered as banned substances in the country of origin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for methods that are able to detect the use of antibiotics administered over the entire life span of an animal, including treatments administered during the first days of the animals’ lives. In previous research focusing on the excretion of oxytetracycline [ 7 ], multiple fluoroquinolones (enrofloxacin, its metabolite ciprofloxacin [ 8 ], and flumequin [ 9 ]) and florfenicol and its metabolite florfenicol amine [ 10 ] to feathers, it has already been shown that antibiotic residues can still be detected in feathers long after treatment. In another study, different antibiotics in feather meal, originating from different countries, were detected, including antibiotics that are registered as banned substances in the country of origin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Love et al, 29 designed a study to build up on previous findings reported in 2007 and 2011 by San Martin et al 9 and Cornejo et al, 10 respectively, regarding the presence of antimicrobials in chicken feathers. Love et al 29 decided to sample feather meals sourced from several states in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…San Martin et al, 9 found that feathers had higher concentrations of enrofloxacin and its metabolite ciprofloxacin than muscle, liver and kidney tissues from birds that had been treated with enrofloxacin. Later on, Cornejo et al, 10 found higher antimicrobial concentration levels in feather matrix than in liver and muscle samples, after the calculated withdrawal period for their formulation had elapsed. Likewise, they found that flumequine was eliminated from feathers more slowly than from other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there was a need for matrices in which antibiotics could be detected over a longer time span. For the monitoring of antibiotic use in poultry, the analysis of feathers provided a means to detect antibiotic residues with a long detection window, even after they were excreted fully from muscle and liver (San Martín et al 2007;Cornejo et al 2011b;Berendsen et al 2013;Cornejo et al 2017;Pokrant et al 2018;Církva et al 2019;Maddaleno et al 2019). Using such a noninvasive method, antibiotic use during almost the whole lifespan of a broiler can be monitored, making it possible to better enforce registration of antibiotics use aiming for prudent application (Jansen et al 2016(Jansen et al , 2017.…”
Section: Introductionmentioning
confidence: 99%